Influence of allium sativum or cinnamomum verum on fermentation of milk and their effects on the physicochemical, biochemical, microbiological and functional properties of probiotic yogurt / Shori, Amal Bakr - Shori, Amal Bakr (2013)

(untitled)
The present study investigated the effects of Allium sativum or Cinnamomum verum water extract on fermentation of milk and subsequent changes in yogurt bacteria growth and fermentation products on the organoleptic, nutritional and functional values of yogurt. Three types of milk (cow, camel and goat) were incubated (41°C) with starter culture in the presence of A. sativum or C. verum water extract until pH of yogurt was reduced to 4.5. The presence of A. sativum or C. verum water extract in cow, camel and goat milk did not affect pH reduction during fermentation whereas titratable acidity (TA) increased only in A. sativum-cow milk yogurt. Both herbal extracts enhanced proteolytic activity only in cow milk during fermentation but the viable cell counts (VCC) increased (p<0.05) in presence of these herbs in all the three types of milk. Further increase (p<0.05) in TA occurred only in A. sativum-cow milk yogurt during storage (4°C). A. sativum or C. verum had no influence on proximate composition for all treatments during storage. The VCC of S. thermophilus in cow- or camel- milk yogurt was not affected by either A. sativum or C. verum during storage but the reverse was true for B. bifidum. The VCC of Lactobacillus spp was higher (p<0.05) in herbal- than plain-camel milk yogurt. The presence of C. verum in the three types of yogurt enhanced the survival of LAB more than the presence of A. sativum after simulated gastrointestinal digestion (SGD). The extent of proteolysis was higher (p<0.05) in presence of A. sativum than presence of C. verum during storage with cow-milk yogurt being more susceptible than camel-milk yogurt. All yogurt showed the highest inhibitory activity of ACE-I on day 7 of storage. The presence of both herbal extracts in the three types of yogurt showed some influence on the extent of proteolysis after SGD but not on ACE-I inhibition activity. Both herbal- cow- and camel-milk yogurt showed increased (p<0.05) α-amylase and α-glucosidase inhibitory activities, antioxidant activity and phenolic contents during 21 days of storage. SGD of herbal- yogurt has no effect on α-amylase and α-glucosidase inhibitory activities and total phenolic content of the three types. However, SGD increased antioxidant activity in all fresh C. verum-yogurt after SGD. The presence of A. sativum or C. verum in cow- and camel- milk yogurt showed improved water holding capacity, susceptibility to syneresis and exopolysaccharides content. However, both herbs affected yogurt rheology properties by showing lesser ability to resist deformation upon applied shear and exhibited shear thinning behaviour. The addition of A. sativum and C. verum did not affect the organoleptic properties of cow- and camel- milk yogurt although A. v sativum reduced the aroma score in the former. The presence of A. sativum or C. verum in milk during yogurt bacteria fermentation can enhance microbial growth and metabolism resulting in an increase in VCC, nutrient digestibility, rheological characteristics and functional properties. The potential stability of yogurt to exposure to digestive enzymes was also enhanced in the present of A. sativum or C. verum.